INSTRUCTIONAL PRACTICES OF SECONDARY TEACHERS AND STUDENTS DURING COVID-19 PANDEMIC - Prasart Nuangchalerm (PEDAGOGIK : JURNAL PENDIDIKAN, 2021)
COVID-19 pandemic can make school and instructional practices at risk. The purpose of this research was to study the teaching and learning activities through an online classroom. The research approach used in this research is a quantitative research approach. The research design used in this study was a survey research design. The type of survey used was a cross-sectional survey design. The choice of a cross-sectional survey design was carried out to measure the behaviour of a number of populations through a sample regarding the level of integrity of the teaching and learning process using online classrooms as a variable in the study. The informants were 23 teachers and 146 students from one secondary school, Mahasarakham province, Thailand. Data were obtained in Semester 2 Academic Year 2020. A questionnaire about online learning was used for data collection through Google form. Mean and standard deviation was employed for data analysis. Findings showed that teachers and students had opinions are at fluctuating level. Some opinions may need discussion for online learning by enhancing technological skills, reskill or upskill in field of educational technology are required for effective instruction.